AN ANALYSIS OF THE MAIN CHARACTERâ€™S CONFLICTS IN â€œTHIRTEEN REASONS WHYâ€ BY JAY ASHER - Dewi, Leila Cynthia; Sutapa, Gatot; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research entitled ?An Analysis of the Main Character?s Conflicts in Thirteen Reasons Why by Jay Asher? was purposed to describe the main character?s conflicts. This research was in qualitative form. The method used is descriptive method. The source of data was taken from the novel Thirteen Reasons Why, published by Razorbill, USA 2007. This novel consists of 288 pages. The data in this research was taken from quotation words, phrases and sentences in the novel Thirteen Reasons Why. The research approach used in this research was structural approach. Based on the results of data analysis, it can be concluded that: First, the internal conflicts that happened to Hannah manifested by disappointment, sadness, confusion, anxiety, fear, suspicion, panic, trauma and boredom. Second, the external conflicts that happened to Hannah between the other characters shown as quarrel, oppression, debate, betrayal, and disagreement. The results of this research, especially for the students in English Education Study Program, are recommended to use this novel as one of the supporting materials for literature. For the readers of Thirteen Reasons Why, it can be used as a material of reflection and self-introspection in the face of reality of daily life that is full of problems. Keywords: Conflicts, Main Character, Novel